Elevated Levels of Cerebrospinal Fluid and Plasma Interleukin-37 in Patients with Guillain-Barré Syndrome. (19th September 2013) - Li, Cong; Zhao, Pingwei; Sun, Xiguang; Che, Yuanyuan; Jiang, Yanfang
Abstract : Aims . Interleukin-37 (IL-37) is an anti-inflammatory cytokine. This study aims to investigate the concentrations of plasma and cerebrospinal fluid (CSF) IL-37 in patients with Guillain-Barré Syndrome (GBS). Methods . The levels of plasma and CSF IL-37, IL-17A, IFN- γ, and TNF- α in 25 GBS patients and 20 healthy controls (HC) were determined by enzyme-linked immunoabsorbent assay and flow cytometric bead array assay, respectively. The values of clinical parameters in the patients were also measured. Results . The concentrations of plasma IL-37, IL-17A, IFN- γ, and TNF- α and CSF IL-37 and IL-17A in patients at the acute phase of GBS were significantly higher than those in the HC. The levels of plasma IL-37, IL-17A, IFN- γ, and TNF- α were positively correlated in those patients, and the levels of CSF IL-37 and IL-17A as well as the levels of plasma TNF- α were correlated positively with the GBS disability scale scores (GDSs) in those patients. Treatment with intravenous immunoglobulin significantly reduced the levels of plasma IL-37, IL-17A, IFN- γ, and TNF- α in the drug-responding patients. Conclusions . Our findings indicate higher levels of plasma and CSF IL-37 and IL-17A and other proinflammatory cytokines in patients with GBS.